Bryophyte Diversity along an Elevational Gradient on Pico Island (Azores, Portugal) - Coelho, Márcia Catarina Mendes (2021)
The study of elevational patterns is a valuable method for inferring the influence of the climate and other variables in the regional distributions of species. Bryophytes are ideal for revealing different environmental patterns in elevational studies, since they occur from sea level to above the tree line. Taking advantage of the long elevational transect of Pico Island and the use of standardized survey methods, our main aims were: (1) to identify and characterize the alpha and beta diversities of bryophytes across the full elevational gradient (12 sites of native vegetation, ranging from 10 to 2200 m above sea level [a.s.l.]); (2) to detect the ecological factors driving bryophyte composition; (3) to identify bryophytes’ substrate specificity; and (4) to check the presence of rare and endemic species. The identification of 878 microplots yielded 141 species (71 liverworts and 70 mosses), almost half of those known to occur on Pico Island. The bryophyte species richness followed a parabolic unimodal pattern with a mid-elevation peak, where the richest native forests occur. A canonical correspondence analysis (CCA) of the bryophyte composition and explanatory variables revealed the effect of the elevation, precipitation, disturbance, richness of vascular plants and bark pH in explaining bryophyte compositions at regional levels. Very few species of bryophytes showed substrate specificity. Pico Island’s elevational gradient could be an asset for studying long-term changes in bryophyte species composition and alpha diversity under global change.